The universal benefits of volunteering a practical workbook for nonprofit organizations, volunteers, and corporations - Pidgeon, Walter Paul (Wiley, 1998)
Provides advice on how to use the concept of return value to recruit, train, and motivate volunteers, and discusses other issues for managers of volunteer programs.
Keywords: aVoluntarism -- zUnited States; aVolunteers -- zUnited States